Romance in Novels Serangkai By Valerie Patkar: Romantisme dalam Novel Serangkai Karya Valerie Patkar - Hana Elisca Sirait; Isnaini Leo Shanty; Fabio Testy Ariance Loren; Dody Irawan; Ahada Wahyusari; Asri Lolita (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This type of research is qualitative using a qualitative descriptive approach. The focus of this research is romance in the novel Serangkai by Valerie Patkar. The aim of this research is to describe the romance contained in the novel Serangkai by Valerie Patkar. The object of this research is the novel Serangkai by Valerie Patkar. The instrument used in this research was the researcher himself because the researcher collected, analyzed and concluded the data. The data collection techniques in this research used listening techniques and note-taking techniques. The data source in this research is the novel Serangkai by Valerie Patkar, and the data in this research are words or sentences, either narrative or dialogue, in the novel that contain romance in the novel Serangkai by Valerie Patkar. The results of this research found that romanticism in literary works consists of seven feelings of romantic emotion, namely the concept of guilt, buried guilt, self-punishment, shame, sadness, hatred and love